The process of latency in current clinical: study through projective methods (Rorschach and T.A.T.). - Tiziana Sola; Carmela Mento; Mariantonietta Gennari; Silvia Marfisi (Mediterranean Journal of Clinical Psychology, 2013)
Our research, based on the contribution of projective methods, by Rorschach Test and the Thematic Apperception Test, should bring us data rather disturbing in so-called normal latencies, particularly in the cohesion of self, organizing drives, the dynamism between phantasy and sense of reality and effectiveness of sinks, allowing us to reflect on the quality of the processes of differentiation and the operation of the transitional spaces, or transformative of the child.